Angular Dependence of Spin Transfer Switching in Spin Valve Nanopillar Based Heusler Alloy. (22nd May 2016) - Khunkitti, Pirat; Kruesubthaworn, Anan; Kaewrawang, Arkom; Mewes, Tim; Mewes, Claudia K. A.; Siritaratiwat, Apirat
Abstract : The spin transfer induced magnetization switching in current perpendicular-to-the-plane spin valve nanopillar based Co2 FeAl0.5 Si0.5 Heusler alloy with varying the initial angles of the magnetization of sensing layer, θ 0, was investigated via macrospin simulations. The effects of an in-plane magnetic field, H i, on the switching behavior were also evaluated. The magnetization switching was excited by spin polarized switching current, I s . The time varying magnetization was computed by the Landau-Lifshitz-Gilbert-Slonczewski equation, while the spin transfer induced noise was examined by using the power spectral density analysis. It was found thatθ 0 should be narrowly initialized since this configuration produces the small noise during the switching. Also, the negativeI s produced more uniform switching than the positiveI s due to existence of ferromagnetic exchange coupling. WhenH i was presented, the noise generated at low frequencies could be suppressed, and then the switching behavior became more uniform. In addition, the results indicated that the noise configuration could be explained by the physical dynamic of magnetization behavior. Hence, the spin transfer induced noise needs to be minimized in order to improve the performance of spin transfer torque random access memory for high density recording.